A facile approach to upconversion crystalline CaF2:Yb3+, Tm3+@mSiO2 nanospheres for tumor therapy. Issue 44 (18th April 2016) - Li, Yangyang; Zhou, Yurong; Li, Xiang; Sun, Jihong; Ren, Zhaohui; Wen, Wengjian; Yang, Xiaoming; Han, Gaorong
Abstract : A new facile approach, namely chemical-assisted sol–gel growth (CASGG), was successfully developed to induce the formation of fine CaF2 :Yb 3+, Tm 3+ nanocrystals within the pore channels of mesoporous silica (mSiO2 ) nanoparticles. Abstract : A new facile approach, namely chemical-assisted sol–gel growth (CASGG), was successfully developed to induce the formation of fine CaF2 :Yb 3+, Tm 3+ nanocrystals within the pore channels of mesoporous silica (mSiO2 ) nanoparticles. A series of upconversion photoluminescent crystalline CaF2 :Yb 3+, Tm 3+ @mSiO2 nanospheres with controlled diameters from ∼65 nm to ∼290 nm were fabricated. All nanospheres presented sound cyto-compatibility and unique ratiometric spectral monitoring functionalities for drug release kinetics. The nanospheres with smallest dimension (UCNP-2.5, ∼65 nm) induced the most sustained DOX release kinetics. More importantly, the in vitro study demonstrated that the DOX loaded UCNP-2.5 nanospheres presented the strongest anti-cancer efficacy to MCF-7 human breast cancer cells due to its stronger penetration ability to cell nuclei due to the size effect.